The Effect of Strategy-Based Instruction on Students’ Speaking Skills atLakidende University - Irawati .; Haryanto .; Syarifuddin Dollah (Universitas Negeri Makassar, 2014)
This study aimed at investigating the effect of strategies-based instruction on students’ speaking skill at Lakidende University and the students’ interest in learning English through strategies-based instruction. This research employed Quasi Experimental Method, with non-equivalent control group design. This research assigned experimental group and control group (30 students for each).Speaking test was used to see the effect of strategies-based instruction on students’ speaking skill and questionnaire was used to see students’ interest in learning English through strategies-based instruction. The data obtained through the speaking test were analyzed by using descriptive statistics and inferential statistics. Meanwhile, the data from questionnaire were analyzed in percentage and descriptive statistics. The students’ speaking skill covered three components: accuracy, fluency, and comprehensibility. The findings showed that there was an improvement on the students’ speaking ability after the treatment. There was a significant difference between the results of post-test of experimental and control group, where the mean score of post-test of experimental group was 70.37, which was higher than the mean score of post-test of control group was 59.63.The value of P-value or sig. (2-tailed) shows that P-value or sig. (2-tailed) is smaller than α (0.00 < 0.05).Furthermore, the data that were collected from questionnaire showed that the students were very high interest toward strategies-based instruction. It is showed by the mean score in scale of 89.6, which was categorized as very high interest. Keywords: effect, strategy-based instruction, speaking skill